Artificial insemination of the Cape honeybee Apis mellifera capensis Esch. and the influence of various factors on success - Buys, B.(Bernard) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1988.